Cardiac allograft vasculopathy: A comprehensive review of diagnostic strategies and therapeutic approaches - Yuxuan Zhang; Ru Liu; Jie Huang; Lijian Gao; Dong Yin (Oncology and Translational Medicine, 2026)
Cardiac allograft vasculopathy (CAV) is the leading cause of late mortality following heart transplantation. This condition is characterized by diffuse coronary intimal hyperplasia driven by both immune and nonimmune mechanisms. This review summarizes the epidemiology, known and emerging risk factors, and complex pathophysiology of CAV. Regarding diagnosis, we evaluate the clinical utility and integration of various modalities, ranging from invasive coronary angiography and high-resolution intravascular imaging (optical coherence tomography) to noninvasive functional assessment (positron emission tomography, cardiovascular magnetic resonance, and computed tomography angiography) and echocardiography. Furthermore, we summarize the most up-to-date evidence regarding pharmacological treatments, percutaneous coronary intervention, coronary artery bypass grafting, and retransplantation, detailing their respective indications and limitations. This review aims to provide an updated framework for the comprehensive understanding and integrated management of CAV while identifying potential areas for future research.